Colorectal Malignancy in a Prospective Irish Inflammatory Bowel Disease Population 15 Years Since Diagnosis: Comparison with the EC-IBD Cohort - Mary Shuhaibar; Colm O’Morain (Gastroenterology Research and Practice)
Background and Aim. As part of the EC-IBD prospective inception cohort study, we had unique opportunity to follow up our patients since diagnosis in the early 1990s. Patients and Methods. All patients from the greater Dublin area (n=192) were followed up from inception between 1991 and 1993 until the 30 September 2009. Patients who developed malignancies were logged electronically with verification of the site and histology. Results. Of the initial 192 patients, 133 were included in the 15-year follow-up. Of those, 80 (60.2%) had UC and 53 (39.8%) had CD. There were 82 (61.7%) males and 51 (38.3%) females. Six patients had extraintestinal malignancy; however, there was no CRC related to IBD noted in our cohort. Four of the 6 identified cases had UC (64%) with a mean age of 54.25 years at the time of cancer diagnosis, whereas the two CD patients had a mean age of 51.5 years at the time of cancer diagnosis. Conclusion. CRC was not observed in our cohort. The six extraintestinal malignancies did not show significant relation to IBD. The high total colectomy rate (in the prebiological therapy era) may have contributed to low malignancy rate.